Nonlinear Schrodinger elliptic systems involving exponential critical growth in R^2 - Francisco S. B. Albuquerque Albuquerque (Electronic Journal of Differential Equations, 2014)
This article concerns the existence and multiplicity of solutions for elliptic systems with weights, and nonlinearities having exponential critical growth. Our approach is based on the Trudinger-Moser inequality and on a minimax theorem.